Compensation and Work Discipline on Teachers’ Performance: A Multifactorial Design - Sihabudin Sihabudin (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this study is to measure the links between compensation and work disciplines towards the teachers’ performance. Underlying the concept of Human Resources Management (HRM) education, this study investigates the effect of the two aforementioned variables on the teacher’s pedagogical approach, classroom activities, and teaching strategies using technology. This research was conducted using a quantitative approach, specifically a multifactorial design. The sample of this current study was 53 people. The data was gathered through test and questionnaires. The data analysis used was a descriptive statistics and multiple linear regression analysis. The results showed that simultaneously the compensation and work discipline variables had a positive and significant effect on the teachers’ performance, and partially compensation and work discipline had a positive and significant effect on the teachers’ performance. The multiple linear regression equation is Y = 20.789 + 0.299X1 + 0.271X2. Meanwhile, the results of the descriptive analysis show that the variables of compensation, work discipline, and teachers’ performance are in a good criteria.